Thoracic spinal cord compression by an atypical aggressive vertebral hemangioma – A case report - More, Bhagirath; Rege, Ishant; Ranade, Deepak; Lachake, Apurva (Nepal Journal of Neuroscience, 2023)
Vertebral hemangiomas are benign vascular lesions of bone , composed of multiple thin-walled vessels surrounded by fat infiltrating the medullary cavity between bony trabeculae.(1) Hemangiomas account for around 2-3% of all spinal tumors and only 0.9-1.2% of these are symptomatic. Surgery is recommended for lesions if they progress rapidly and cause neurological deficits. 47 years old female patient presented with bilateral lower limb weakness due to an aggressive atypical vertebral body hemangioma at D7 level. Patient underwent pre-op embolisation with surgical decompression and stabilization. Neurological recovery was almost complete over a period of 2 months.